Staging models in eating disorders: A systematic scoping review of the literature - E. Tomba; L. Tecuta; V. Gardini; G. Tomei; E. Lo Dato (Comprehensive Psychiatry, 2024)
Eating Disorders (ED) are characterized by low remission rates, treatment drop-out, and residual symptoms. To improve assessment and treatment of ED, the staging approach has been proposed. This systematic scoping review is aimed at mapping the existing staging models that explicitly propose stages of the progression of ED.A systematic search of PubMed, PsycINFO, Scopus was conducted with the terms staging, anorexia nervosa, bulimia nervosa, binge-eating disorders, eating disorders. Eleven studies met inclusion criteria presenting nine ED staging models, mostly for anorexia nervosa. Three were empirically tested, one of which was through an objective measure specifically developed to differentiate between stages. Most staging models featured early stages in which the exacerbation of EDs unfolds and acute phases are followed by chronic stages. Intermediate stages were not limited to acute stages, but also residual phases, remission, relapse, and recovery. The criteria for stage differentiation encompassed behavioral, psychological, cognitive, and physical features including body mass index and illness duration. One study recommended stage-oriented interventions. The current review underscores the need to empirically test the available staging models and to develop and test new proposals of staging models for other ED populations. The inclusion of criteria based on medical features and biomarkers is recommended. Staging models can potentially guide assessment and interventions in daily clinical settings.